Intraoperative neurophysiological monitoring in selective dorsal rhizotomy (SDR). Issue 1 (March 2020) - Jiang, Wenbin; Zhan, Qijia; Wang, Junlu; Mei, Rong; Xiao, Bo
For decades, intraoperative neurophysiological monitoring (IONM) has been used to guide selective dorsal rhizotomy (SDR) for the treatment of spastic cerebral palsy (CP). Electromyography (EMG) interpretation methods, which are the core of IONM, have never been fully discussed and addressed, and their importance and necessity in SDR have been questioned for years. However, outcomes of CP patients who have undergone IONM-guided SDR have been favorable, and surgery-related complications are extremely minimal. In this paper, we review the history of evolving EMG interpretation methods as well as their neuroelectrophysiological basis.